Heat, cold and pressure induced denaturation of proteins. Issue 2 (2003) - Panick Panick, G. G.; Herberhold Herberhold, H. H.; Sun Sun, Z. Z.; Winter Winter, R. R.
Abstract : We studied the pressure‒induced unfolding and refolding of monomeric proteins, such as SNase, α‒chymotrypsin and ubiquitin, by using synchrotron X‒ray small‒angle scattering and Fourier‒transform infrared spectroscopy, which monitor changes in the tertiary and secondary structural properties of the proteins upon pressurization. Furthermore, by using the pressure‒jump relaxation technique in combination with time‒resolved X‒ray diffraction and infrared spectroscopy, the kinetics of the unfolding/refolding of the proteins, was investigated. Significant differences in secondary structure and chain compactness in the folding/unfolding reactions of these proteins are observed. The results are compared with data obtained from other methods of denaturation, such as heat and pressure‒assisted cold denaturation. The cold‒ and pressure‒induced unfolding both yield a particularly unfolded state characterized by a persistent amount of secondary structure.